Evaluation of productive and reproductive performance of Black Bengal goat - Paul, RC; Rahman, ANMI; Debnath, S; Khandoker, MAMY (Bangladesh Journal of Animal Science, 2014)
The present study was conducted with a view to know the productive and reproductive parameters of Black Bengal goat in a nucleus breeding flock of Bangladesh Agricultural University, and two other regions i.e., Modhupur (Tangail) and Dimla, (Nilphamari). Data were collected on a regular basis from January 2011 to January 2012. The results showed that birth weight of kids was significantly affected by type of birth (p<0.01), parity of dam (p<0.01) and season of birth (p<0.05) in three different regions. Yearling weight was varied significantly by sex of kid (p<0.01) and season of birth (p<0.05) in three different regions. Daily milk production was significantly affected by type of birth (p<0.01), parity of dam (p<0.01) and season of birth (p<0.01). Litter size and age at first conception were significantly affected by parity of dam. Kid mortality was significantly affected by season of birth (p<0.01) in nucleus flock. The results indicated that sex of kid, type of birth, parity of dam and season of birth influenced the productive and reproductive parameters in nucleus flock, Modhupur and Dimla and the performance also varied between nucleus flock and field levels. DOI: http://dx.doi.org/10.3329/bjas.v43i2.20704 Bang. J. Anim. Sci. 2014. 43 (2): 104-111